Building survivor activism: An organisational view - Sadiq-Tang, Shameem (Torture Journal, 2018)
The purpose of this perspectives paper is to share how different models of survivor activism can be built in a clinical charity with a human rights ethos and to set out the value that has come from growing survivor activism organically, based on experiences at Freedom from Torture.